Predictors of cognitive and physical decline: Results from the Health Aging and Body Composition Study - Handing, Elizabeth P.; Hayden, Kathleen M.; Leng, Xiaoyan Iris; Kritchevsky, Stephen B. (Frontiers in Aging Neuroscience, 2023)
Background: Risk factors for cognitive decline and physical decline have been studied independently, however older adults might experience decline in both areas i.e., dual decline. Risk factors associated with dual decline are largely unknown and has significant implications on health outcomes. Methods: Using data from the Health, Aging and Body Composition (Health ABC) study, a longitudinal prospective cohort study, we examined trajectories of decline based on repeated measures of the Modified Mini-Mental State Exam and the Short Physical Performance Battery across 6 years. We calculated four mutually exclusive trajectories of decline and explored predictors of decline: cognitive decline (n=306), physical decline (n= 231), dual decline (n= 110), and reference group (n= 905). Results: Multinomial logistic regression tested the association of 17 baseline risk factors with decline. Odds of dual decline where significantly higher for individuals at baseline with depressive symptoms (CES-D >16) (Odds Ratio (OR)=2.49, 95% Confidence Interval (CI): 1.05-6.29), ApoE-ε4 carrier (OR= 2.09, 95% CI: 1.06-1.95), or if they had lost 5+lbs in past year (OR=1.79, 95% CI: 1.13-2.84). Odds were significantly lower for individuals with a better score on the Digit Symbol Substitution Test (per standard deviation (OR per SD: 0.47, 95% CI 0.36-0.62) and faster 400-meter gait (OR per SD= 0.49, 95% CI: 0.37-0.64). Conclusion: Among predictors, depressive symptoms at baseline significantly increased the odds of developing dual decline but was not associated with decline in the exclusively cognitive or physical decline groups. APOE-ε4 status increased the odds for cognitive decline and dual decline but not physical decline. More research on dual decline is needed because this group represents a high risk, vulnerable subset of older adults.